READINESS OF E-GOVERNMENT IMPLEMENTATION IN DEVELOPING COUNTRIES IN THE PERSPECTIVE OF THE GOVERNMENTAL MODELS: A CASE IN INDONESIA - Orbawati, Eny Boedi; Nugraha, Joko Tri; Fadlurahman, Fadlurahman; Mukti, Ari; Sugiharti, Retno (Sosiohumaniora, 2025)
Studies regarding e-Government readiness have become a mushrooming issue in developing countries. To contribute to discussions in the context of the Indonesian government, this research was designed to analyze 1 specifically) the level of readiness of the Magelang City Government, Indonesia, in implementing e-government from a government model perspective, and 2) obstacles in developing e-government-based public services in the city. Research data was collected through in-depth interviews, documentation, and observation. We used qualitative content analysis to analyze the data. The findings of this research contribute to finding the root cause of the government's unpreparedness to implement smart governance-based public services in Indonesia. The research results show that E-Government is defined as an effort to increase the effectiveness and efficiency of public services by using information and communication technology. The implementation of e-government by the Magelang City Government aims to provide more effective public services. However, the findings show that the implementation of e-government is not yet efficient because it needs to be improved at the interaction stage. Factors inhibiting the development of e-government in Magelang City include very limited human resources with IT qualifications (only 17 people), inadequate archivist staff, disturbed vision, and a strategy that does not have information system integration management in each Regional Apparatus Organization.